Chemical and Microbiological Quality of Dry Fish from Kakinada - M.M., Prasad; C.C., Panduranga Rao; S.S., Gupta (Fishery Technology, 2025)
Chemical and microbiological qualities of 75 samples of dry fish from local markets were studied. In most of the samples, moisture content was found to be higher and salt content lower as compared with ISI specifications for cured dried fish. Potential pathogens, Escherichia coli and coagulase positive staphylococci, were isolated from some of the samples